2020
DOI: 10.32615/ps.2019.173
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - The JIP-test as a tool for forestry in times of climate change

Abstract: Replicate common gardens of Italian and Greek provenances of Quercus ilex, Q. pubescens, and Q. frainetto seedlings were established in 2017 in Italy, Greece, and Germany (here: also Q. robur) to assess their potential for plantations for future climate scenarios. The JIP-test was applied on saplings (2016) and in the summers of 2017-2019 to assess the efficiency of the photosynthetic apparatus. Seedlings from the nurseries differed in the tested JIP parameters from older plants in the field. Further, consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…By disassembling the predawn values of PI abs into its components, not only φP0 but also RC/ABS and ψE0 were enhanced (Fig. 1S) in the SWA common garden, consistent with the results of Bantis et al (2020). Interestingly, solely the plants in SWA showed a significant decrease of φP0 predawn values (Fig.…”
Section: Differences Between Oak Species and Provenances Under Contra...supporting
confidence: 82%
See 2 more Smart Citations
“…By disassembling the predawn values of PI abs into its components, not only φP0 but also RC/ABS and ψE0 were enhanced (Fig. 1S) in the SWA common garden, consistent with the results of Bantis et al (2020). Interestingly, solely the plants in SWA showed a significant decrease of φP0 predawn values (Fig.…”
Section: Differences Between Oak Species and Provenances Under Contra...supporting
confidence: 82%
“…Similarly, we detected no clear differences between the studied oak provenances. Better performance of the Greek vs. the Italian provenance, in line with Bantis et al (2020), was observed only in terms of PIabs (Fig. 2F), among all tested parameters.…”
Section: Differences Between Oak Species and Provenances Under Contra...mentioning
confidence: 57%
See 1 more Smart Citation
“…Chlorophyll fluorescence has been successfully used in applied research to evaluate the effects of stressors on tree seedlings and small plants and to screen genotypes adapted to specific environmental conditions (Kuhlgert et al, 2016;Çicȩk et al, 2020;Dimitrova et al, 2020). ChlF analysis has been used by Bantis et al (2020); Bantis et al (2021); Bashir et al, (2021) and Pollastrini et al (2020) to select tree species for reforestation under climate change conditions by analysing the results of a system of community gardens across Europe. ChF is also applied in nurseries to determine young tree vigour and potential seedling performance (Perks et al, 2001;L'Hirondelle et al, 2007), stand quality (Binder et al, 1996), and winter hardiness (Fisker et al, 1995).…”
Section: Conclusion: Advantages and Limitationsmentioning
confidence: 99%
“…Chlorophyll fluorescence has been successfully used in applied research to evaluate the effects of stressors on tree seedlings and small plants and to screen genotypes adapted to specific environmental conditions ( Kuhlgert et al., 2016 ; Çiçek et al., 2020 ; Dimitrova et al., 2020 ). ChlF analysis has been used by Bantis et al. (2020) ; Bantis et al (2021) ; Bashir et al., (2021) and Pollastrini et al.…”
Section: Conclusion: Advantages and Limitationsmentioning
confidence: 99%